A wali’s quest for guidance; The Islamic genealogies of the Seh Mlaya - Meyer, Verena (Wacana, Journal of the Humanities of Indonesia, 2021)
The Seh Mlaya is a narrative tradition of Sunan Kalijaga’s conversion and becoming a wali that is well-known for its drawing on pre-Islamic narrative and discursive legacies. In this article, I explore the Islamic genealogies of the narrative as told in a Surakarta manuscript (RP 333). I argue that the author uses the verse narrative to articulate two prominent, yet seemingly opposed, intellectual and spiritual traditions in Islamic Java and the relation between them: the speculative and ecstatic teachings of the Sufi lineage of the Syattariyah on the one hand, and Ghazālī’s work with its emphasis on obedience and the purification of the soul on the other. Sunan Kalijaga’s quest narratively holds together these two currents and even gestures at a transcendence of their difference as Sunan Kalijaga’s efforts, even as they fail, lead to his realization of guidance.